Women’s recovery & reconstruction of self after intimate partner violence - Cavilli, S.; Coates, Rosemary; Maycock, B. (Blackwell Publishing Inc., 2015)
Introduction: For women in Australia, sexual assault, domestic and family violence are some of the most pervasive human rights violations. According to the Australian Bureau of Statistics (2005) nearly one in five Australian women has experienced violence by a current or previous intimate partner. Research on intimate partner abuse and violence (IPV) has focused on factors related to a woman's decision to leave or stay and the processes involved in arriving at that decision. However, studies on IPV have seldom ventured beyond the point of physical separation and little is known about the experience of women who have permanently left their abusive partners. The oppressive nature of the abusive relationship leads to restricted personal growth as survival was prioritised over self-development. Consequently, the post-separation period affords opportunities for redirection of energy and intention and extrication from false beliefs of their characteristics and identity. Objectives: The aim of this research is to establish theory that predicates the construction of a woman's self-identity, personal strength and agency after the permanent physical separation from an abusive relationship. Methods: This qualitative, grounded theory research utilised explorative interviews with women, who permanently separated from an IPV relationship, as the main source of data. Results & Discussion: The resultant framework will prove greater depth in understanding the women's process of leaving and recovery from IPV and what has assisted them in regaining their psychological, emotional and sexual equilibrium.